Mail‐out bowel cancer screening: Identifying the behavioural stumbling blocks. Issue 5 (30th December 2021) - Myers, Larry; Goodwin, Belinda C.; Ireland, Michael; March, Sonja; Aitken, Joanne
Abstract: Objective: To describe the actions taken by recipients of mail‐out faecal occult blood test (FOBT) kits and to identify the points at which progress towards kit completion typically stops. Differences according to gender, age, and screening intention were also examined. Methods: 1599 people completed an online survey identifying the actions they took upon receiving an FOBT kit. Latent class analysis was conducted to identify latent subgroups of participants that reported similar actions. Differences between gender, age, and intention status were assessed using non‐invariance testing. Results: Four latent subgroups of FOBT invitees were identified: those who complete and return their FOBT kit ('completers'); those who bring the kit into their house but go no further ('ignorers'); those who open the package and read the bowel cancer information materials but go no further ('readers'); and those who read the instructions but do not place the kit near the toilet and do not complete their FOBT kit ('leavers'). Non‐completers who intended to use the kit were most likely to be in the 'leavers' class, while those who had no intention were most likely to be in the 'readers' class. Conclusions: Distinct subgroups of non‐responders exist among bowel cancer screening invitees, suggesting different behaviour change interventions are needed to facilitate participation. Some invitees, especially those with high participatory intention, are likely to benefit from prompts to take the kit into the toilet, while others, with little participatory intention, often read the invitation materials presenting an opportunity to intervene with health messages.